Endovascular therapy for advanced post-thrombotic syndrome: Proceedings from a multidisciplinary consensus panel. (August 2016) - Vedantham, Suresh; Kahn, Susan R; Goldhaber, Samuel Z; Comerota, Anthony J; Parpia, Sameer; Meleth, Sreelatha; Earp, Diane; Williams, Rick; Sista, Akhilesh K; Marston, William; Rathbun, Suman; Magnuson, Elizabeth A; et al.
Patients with advanced post-thrombotic syndrome (PTS) and chronic iliac vein obstruction suffer major physical limitations and impairment of health-related quality of life. Currently there is a lack of evidence-based treatment options for these patients. Early studies suggest that imaging-guided, catheter-based endovascular therapy can eliminate iliac vein obstruction and saphenous venous valvular reflux, resulting in reduced PTS severity; however, these observations have not been rigorously validated. A multidisciplinary expert panel meeting was convened to plan a multicenter randomized controlled clinical trial to evaluate endovascular therapy for the treatment of advanced PTS. This article summarizes the findings of the panel, and is expected to assist in developing a National Institutes of Health-sponsored clinical trial and other studies to improve the care of patients with advanced PTS.